FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU FOOD WASTE PADA IBU RUMAH TANGGA DI RW 019 KELURAHAN CILANGKAP KOTA DEPOK TAHUN 2023 - Rania Adythasari (2023)
Food waste primarily originated from households. The behavior of housewives towards food played a significant role in the occurrence of food waste. The amount of food waste generated in UPS Cilangkap in 2021 was 1,583,642 kg, which was the highest in Depok City. The aim of this research was to analyze factors related to food waste behavior among housewives in RW 019, Cilangkap Village in 2023. The research was conducted from February to June 2023. The method used in this research was quantitative with a cross-sectional study design. The research sample consisted of 109 respondents from housewives in RW 019, Cilangkap Village, using the cluster random sampling technique. The instrument used was a questionnaire. The research results indicated that the majority of respondents exhibited less-than-desirable behaviors towards food waste (55%). Based on the chi-square test analysis, the factors related to food waste behavior were employment status (p-value = 0.03), attitude (p-value = 0.006), and food management behavior (p-value = 0.016). In conclusion, the behavior of food waste among housewives in RW 019, Cilangkap Village in 2023, was influenced by employment status, attitudes, and the management of food management behavior, with the hope that housewives could apply good food management practices.